PENGARUH MOTIVASI BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA - Umami, Moh Rizal (STKIP La Tansa Mashiro, 2022)
The purpose of this study was to analyze the effect of motivation and independent learning on students' mathematics learning achievement. The method used is survey method. Data collection techniques were carried out by giving questionnaires to students. The samples taken came from the population of class VII SMPN 2 Warunggunung. Before testing the hypothesis, the validity of the items in the form of a questionnaire was tested. The research sample consisted of 37 students of class VII SMPN 2 Warunggunung, the samples were obtained using a proportional random sampling technique. The results obtained in the study were 1) learning motivation had a significant effect on students' learning outcomes in learning mathematics, 2) learning independence had a significant effect on students' learning outcomes in learning mathematics, 3) learning motivation and learning independence had an effect on students' mathematics learning achievement. This can be interpreted that the acquisition of student learning outcomes can be increased by considering the motivational factors and student learning independence.Keywords: learning motivation, learning independence, learning achievement